2018
DOI: 10.3390/ijgi7070244
|View full text |Cite
|
Sign up to set email alerts
|

Shaking Maps Based on Cumulative Absolute Velocity and Arias Intensity: The Cases of the Two Strongest Earthquakes of the 2016–2017 Central Italy Seismic Sequence

Abstract: By referring to the two strongest earthquakes of the 2016-2017 Central Italy seismic sequence, this paper presents a procedure to make shaking maps through empirical relationships between macroseismic intensity and ground-motion parameters. Hundreds of waveforms were processed to obtain instrumental ground-motion features which could be correlated with the potential damage intensities. To take into account peak value, frequency, duration, and energy content, which all contribute to damage, cumulative absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…On the other hand, correlation between residuals — which is the focus of this study — generally requires additional modeling. For instance, a few studies, such as Foulser‐Piggott and Stafford, 17 Bradley, 23 Du and Wang, 24 Costanzo, 25 Bullock, 26 and Schiappapietra and Douglas 27 (hereafter denoted as FS2012, B2010, DW2013, C2018, B2019, and SD2020, respectively), have investigated the spatial correlation in integral IM residuals by employing classical geostatistical methods, through semivariograms within short interstation distances. These studies have shown that the spatial correlation model parameters vary greatly from event to event.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, correlation between residuals — which is the focus of this study — generally requires additional modeling. For instance, a few studies, such as Foulser‐Piggott and Stafford, 17 Bradley, 23 Du and Wang, 24 Costanzo, 25 Bullock, 26 and Schiappapietra and Douglas 27 (hereafter denoted as FS2012, B2010, DW2013, C2018, B2019, and SD2020, respectively), have investigated the spatial correlation in integral IM residuals by employing classical geostatistical methods, through semivariograms within short interstation distances. These studies have shown that the spatial correlation model parameters vary greatly from event to event.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 4 represents the workflow implemented to generate damage scenarios in case of an earthquake occurs. The workflow can be summarized in these steps: Once THIS detects a new earthquake with potential effects on the monitored areas, the earthquake time-histories are extracted and pre-processed as described in the previous paragraph; At this point, another control verifies if the maximum absolute acceleration is greater than 1 cm/s 2 ; in the affirmative case, the Python script calculates the rotation-invariant parameters of the ground-motion [ 54 ] to take into account frequency, duration, and energy content, which together can contribute to structural damage [ 55 ]: Peak Ground Acceleration, Pseudo-Spectral Accelerations, Arias Intensity [ 56 ], Standard Cumulative Absolute Velocity [ 57 ]. By interpolating the measured PGAs using the inverse distance weighted (IDW) technique [ 58 ] through the ArcPy module for Python [ 59 ], a map covering the whole built-up area is obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Once THIS detects a new earthquake with potential effects on the monitored areas, the earthquake time-histories are extracted and pre-processed as described in the previous paragraph; • At this point, another control verifies if the maximum absolute acceleration is greater than 1 cm/s 2 ; in the affirmative case, the Python script calculates the rotation-invariant parameters of the ground-motion [54] to take into account frequency, duration, and energy content, which together can contribute to structural damage [55]: Peak Ground Acceleration, Pseudo-Spectral Accelerations, Arias Intensity [56], Standard Cumulative Absolute Velocity [57].…”
mentioning
confidence: 99%
“…For each of the waveforms, the peak values of the acceleration can be easily obtained, allowing the construction of urban-scale shake maps. Figure 12 is a shake map obtained from the detected event, obtained using python code; for more clarification, refer to [3,24].…”
Section: Camerino Networkmentioning
confidence: 99%